Service Quality and Passenger Satisfaction on the Coastal Routes of Southwest Crete - Sitzimis, Ioannis (Transactions on Maritime Science, 2024)
The aim of this paper is to validate the correctness of the defining variables (categories) used by Sitzimis (2024a) to measure the quality of services provided on the coastal lines of southwest Crete. In this context it tries to determine both how much they affect the overall passenger satisfaction and which one is the most important. This research is both novel and distinct and could hopefully be expanded to include comparable coastal routes around the world and other means of transport. It is also expected to benefit shipowners, passengers, and policymakers by maintaining the level of services provided at a satisfactory level. Methodologically, we have used confirmatory factor analysis to determine the real factors affecting the quality of coastal services in southwest Crete. A non-parametric correlation test has been applied between the degree of satisfaction and the above factors. It has shown that there is a moderate positive correlation. We have tested through multiple regression both the extent to which these factors have an impact on passengers’ satisfaction and their relative significance. The resulting evaluation factors are "comfort, safety, land and on-board services", "pricing policy" and "route reliability". They have predicted 63.5% of passengers’ satisfaction variance and the first factor is the most significant. Their improvement is expected to stimulate the users’ satisfaction. Ιt appears that the five categories used by Sitzimis, and their hierarchical classification, have not been fully confirmed by the factor analysis.